ANALISIS KEKASARAN MOLDING BERBASIS ADDITIVE MANUFACTURING MATERIAL POLYLACTIC ACID - Hafiz, Muhammad Al; Junaidi, Ahmad; Sundari, Ella (MACHINERY Jurnal Teknologi Terapan, 2022)
At this time the development of technology has moved very fast. Humans need technology to facilitate every activity, 3D Printers continue to develop and are widely used in various countries. 3D printing uses a special printing machine to produce three-dimensional shapes. Molding or molding is a production process by forming raw materials using a rigid frame or model called a mold. This research was conducted to change the function of 3D printing which is usually to print prototypes into molds. as well as knowing the level of roughness of the mold that is printed. analysis using ANOVA that has been applied, it can be concluded that layer height: low, standard, high has an effect on the roughness of the printed molding, and it can be proven in the discussion chapter with Fcount 3.150 > Ftable 2.56. with a significant 0.034 < 0.05. and the lowest roughness results are printed using a layer height: 0.16 mm/s (high quality).